A Systematic Literature Review of the Blood Supply Chain through Bibliometric Analysis and Taxonomy - Imamoglu, Gul; Topcu, Y. Ilker; Aydin, Nezir (MDPI, 2023)
The blood supply chain is an inseparable part of health systems. The importance of blood and the difficulties of managing the blood supply chain have led to numerous publications on this topic over the last two decades. This study seeks to reveal the state of the art of the blood supply chain and provide research gaps and future research directions. For this purpose, a mixed review methodology is conducted that includes bibliometric analysis, network analysis, and a six-dimension taxonomy. Bibliometric analysis identifies the most contributing journals, authors, and countries as well as provides popular keywords, while network analysis reveals interactions between these components. Taxonomy clarifies decision models and research gaps with a deeper examination. The electronic database Web of Science is examined to uncover relevant articles. In total, 265 articles are analyzed in detail. The findings reveal that the blood supply chain gathers more interest from researchers, and despite the continuing dominance of the inventory stage, there is an upward trend in the literature for the research of the blood supply chain as a whole. Optimization techniques come forward in the blood supply chain topic as solution methodology. In accordance with the results of bibliometric analysis, network analysis, and taxonomy, six prospective directions for future research are emphasized.
Keywords: blood supply chain; literature review; bibliometric analysis; network analysis; taxonomy; VEHICLE-ROUTING PROBLEM; INVENTORY MANAGEMENT; PLATELET PRODUCTION; NETWORK DESIGN; PROGRAMMING-MODEL; SHELF-LIFE; TECHNICAL EFFICIENCY; CITATION ANALYSIS; ISSUING POLICIES; OPTIMIZATION; Social Sciences - Other Topics